Pathologically noninvasive cancer predictors and surgical procedure for peripheral lung cancer. Issue 3 (22nd November 2022) - Tsuchida, Hiroyuki; Tanahashi, Masayuki; Suzuki, Eriko; Yoshii, Naoko; Watanabe, Takuya; Yobita, Shogo; Uchiyama, Suiha; Iguchi, Kensuke; Nakamura, Minori; Endo, Takumi
Abstract: Background: In this retrospective study, based on recent studies reporting the superiority of sublobar resection to lobectomy for peripheral small size non‐small cell lung cancer (NSCLC), we investigated the optimal pathological factors for predicting noninvasive cancer and the selection of operative procedure. Methods: Patients with peripheral NSCLC of ≤2 cm who underwent surgery at our hospital between January 2010 and June 2020 were included in this study. We evaluated the relationship between pathologically noninvasive cancer and predictive factors according to the area under the curve (AUC) and accuracy, and the cutoff value was set to investigate indications for sublobar resection. Results: The comparison of the AUCs revealed that the maximum standardized uptake value and consolidation to tumor (C/T) volume ratio were better predictors than the C/T ratio. Among the three factors, the C/T volume ratio showed the best accuracy. The patients were divided into two groups (low and high) using the cutoff value of the C/T volume ratio and compared according to the surgical procedure (lobectomy vs. segmentectomy). In the low‐group, there was no significant difference in the prognosis. In the high‐group, the 5‐year recurrence‐free survival rate of the patients who received lobectomy was 87.8%, while that of patients who received segmentectomy was 75.8% ( p  = 0.08). Conclusions: The C/T volume ratio was the best preoperative pathologically noninvasive predictive factor. Sublobar resection should be performed with caution in cases with significant solid components on three‐dimensional images. Abstract : The consolidation to tumor ratio of volume was the best preoperative pathologically noninvasive predictive factor. Sublobar resection should be performed with caution in cases with significant solid components on three‐dimensional images.